Low seroprevalence rates of Zika virus in Kuala Lumpur, Malaysia. (11th July 2019) - Sam, I-Ching; Montoya, Magelda; Chua, Chong Long; Chan, Yoke Fun; Pastor, Andrew; Harris, Eva
Abstract: Background: Zika virus (ZIKV) is believed to be endemic in Southeast Asia. However, there have been few Zika cases reported to date in Malaysia, which could be due to high pre-existing levels of population immunity. Methods: To determine Zika virus (ZIKV) seroprevalence in Kuala Lumpur, Malaysia, 1085 serum samples from 2012, 2014–2015 and 2017 were screened for anti-ZIKV antibodies using a ZIKV NS1 blockade-of-binding assay. Reactive samples were confirmed using neutralization assays against ZIKV and the four dengue virus (DENV) serotypes. A sample was possible ZIKV seropositive with a ZIKV 50% neutralization (NT50 ) titre ≥20. A sample was probable ZIKV seropositive if, in addition, all DENV NT50 titres were <20 or the ZIKV NT50 titre was >4-fold greater than the highest DENV NT50 titre. Results: We found low rates of possible ZIKV seropositivity (3.3% [95% confidence interval CI 2.4 to 4.6]) and probable ZIKV seropositivity (0.6% [95% CI 0.3 to 1.4]). Possible ZIKV seropositivity was independently associated with increasing age (odds ratio [OR] 1.04 [95% CI 1.02 to 1.06], p<0.0001) and male gender (OR 3.5 [95% CI 1.5 to 8.6], p=0.005). Conclusions: The low ZIKV seroprevalence rate, a proxy for population immunity, does not explain the low incidence of Zika in dengue-hyperendemic Kuala Lumpur. Other factors, such as the possible protective effects of pre-existing flavivirus antibodies or reduced transmission by local mosquito vectors, should be explored. Kuala Lumpur is at high risk of a large-scale Zika epidemic.